2011
DOI: 10.1021/ci100334z
|View full text |Cite
|
Sign up to set email alerts
|

Automated Information Extraction and Structure−Activity Relationship Analysis of Cytochrome P450 Substrates

Abstract: Information on CYP-chemical interactions was comprehensively explored by a text-mining technique, to confirm our previous structure-activity relationship model for CYP substrates (Yamashita et al. J. Chem. Inf. Model. 2008, 48, 364-369). The text-mining technique is based on natural language processing and can extract chemical names and their interaction patterns according to sentence context. After chemicals were automatically extracted and classified into CYP substrates, inhibitors, and inducers, 709 substra… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
30
0

Year Published

2011
2011
2014
2014

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 18 publications
(30 citation statements)
references
References 22 publications
0
30
0
Order By: Relevance
“…P450s were already the subject of many QSAR studies (Ekins et al, 1999;Lewis et al, 2001;Riley et al, 2001;Wanchana et al, 2003;Hansch et al, 2004;Mao et al, 2006;Gleeson et al, 2007;Yamashita et al, 2008Yamashita et al, , 2011 as well as inhibitor/noninhibitor classification studies (Jensen et al, 2007;Choi et al, 2009;Cheng et al, 2011). For large ADME/Tox characterization panels, it has been repeatedly found that molecular size plays a major, defining role.…”
Section: Resultsmentioning
confidence: 99%
“…P450s were already the subject of many QSAR studies (Ekins et al, 1999;Lewis et al, 2001;Riley et al, 2001;Wanchana et al, 2003;Hansch et al, 2004;Mao et al, 2006;Gleeson et al, 2007;Yamashita et al, 2008Yamashita et al, , 2011 as well as inhibitor/noninhibitor classification studies (Jensen et al, 2007;Choi et al, 2009;Cheng et al, 2011). For large ADME/Tox characterization panels, it has been repeatedly found that molecular size plays a major, defining role.…”
Section: Resultsmentioning
confidence: 99%
“…Based on trees from Lewis et al [34]., Terfloth et al [35]., Yamashita et al [36]. and Zhang et al [37].…”
Section: Decision Tree For Cyp Isoform Predictionmentioning
confidence: 99%
“…Information extraction methods applied to extract structured data from publications have been studied extensively in the past in fields that include biology (BarbosaSilva et al, 2010, Corney et al, 2004, Meurs et al, 2011, chemistry (Na et al, 2010, Yamashita et al, 2011, biomedicine (Bundschus et al, 2008, Crowley et al, 2010, Pestian et al, 2007, text summarisation (Lin and Hovy, 2000) and e-learning (Monachesi et al, 2009). A review of these previous efforts is provided in this section.…”
Section: Related Workmentioning
confidence: 99%
“…Furthermore, similar approaches (ontology-based GATE gazetteer and relation extraction using pre-defined rules, and machine-learning) have been applied with mixed success to publications in the bioinformatics field (Barbosa-Silva et al, , Bundschus et al, 2008, Corney et al, 2004, Crowley et al, 2010, Meurs et al, 2011, Na et al, 2010, Pestian et al, 2007, Yamashita et al, 2011. Further examples are provided in the following paragraphs.…”
Section: Related Workmentioning
confidence: 99%
See 1 more Smart Citation